Leveraging AI for Sustainable Supply Chain Management in Retail: Utilizing Machine Learning for Carbon Footprint Reduction, Resource Optimization, and Circular Economy Integration - Sricharan Kodali, (Newark Journal of Human-Centric AI and Robotics Interaction, 2025)
In the context of increasing environmental awareness and regulatory pressure, the retail industry faces the imperative of transforming its supply chain practices to align with sustainability objectives. This paper delves into the utilization of Artificial Intelligence (AI) and machine learning techniques to enhance sustainable supply chain management within the retail sector. The study provides a comprehensive examination of how AI can be harnessed to achieve significant reductions in carbon footprint, optimize resource utilization, and integrate circular economy principles into retail supply chains.The application of AI in this domain is multifaceted, encompassing several critical areas. Machine learning algorithms facilitate advanced predictive analytics that enhance supply chain forecasting accuracy, thereby minimizing excess production and waste. These predictive models leverage vast datasets, including historical sales data, seasonal trends, and market conditions, to improve inventory management and reduce overstock scenarios that contribute to unnecessary environmental strain. By optimizing inventory levels and demand forecasting, retailers can substantially diminish their carbon footprint associated with logistics and storage.Resource optimization is another pivotal area where AI plays a transformative role. Through the deployment of sophisticated machine learning models, retailers can analyze and optimize the allocation of resources across their supply chains. These models can evaluate factors such as transportation routes, supplier performance, and material usage, leading to more efficient processes and reduced resource consumption. Machine learning-driven insights enable retailers to implement more sustainable practices, such as optimizing transportation routes to decrease fuel consumption and selecting suppliers with lower environmental impact.The integration of circular economy principles into supply chain management is facilitated by AI through the development of closed-loop systems. AI technologies enable retailers to track and manage products throughout their lifecycle, from production to end-of-life. This capability supports the creation of circular supply chains where products are designed for reuse, remanufacturing, or recycling, thus minimizing waste and extending product lifecycles. AI-driven frameworks for circular economy integration facilitate the identification of opportunities for product take-back programs, recycling initiatives, and the repurposing of materials, contributing to the overarching goal of reducing environmental impact.The paper also explores the development of AI-driven frameworks designed to promote waste reduction and efficiency in resource utilization. These frameworks employ machine learning techniques to analyze and optimize various aspects of supply chain operations, including production scheduling, logistics management, and inventory control. By leveraging real-time data and predictive analytics, these frameworks enhance decision-making processes, leading to more sustainable supply chain practices and improved corporate social responsibility outcomes.Through a detailed review of case studies and real-world implementations, the paper highlights the tangible benefits and challenges associated with integrating AI into sustainable supply chain management. Case studies from leading retail organizations illustrate the practical applications of AI-driven solutions and their impact on reducing carbon emissions, optimizing resource usage, and fostering a circular economy. The paper also addresses potential obstacles, such as data privacy concerns, integration complexities, and the need for continuous model updates to ensure ongoing effectiveness.The paper advocates for the adoption of AI technologies as a strategic enabler for sustainable supply chain management in retail. By leveraging machine learning for carbon footprint reduction, resource optimization, and circular economy integration, retailers can not only achieve significant environmental benefits but also enhance their operational efficiency and corporate reputation. The research underscores the importance of continued innovation and investment in AI-driven solutions to advance sustainability objectives and contribute to the broader goals of environmental conservation and social responsibility.